The Mask of the Warrior: unraveling deep-seated health vulnerabilities in veteran identities - Grimell, Jan (Frontiers in Sociology, 2024)
As service members transition from deployment to civilian life, they are also expected to reintegrate into society. An important part of this process is to “soften up” veteran or warrior identities and open up the self for both existing and new identities, mindsets, and ways of life. Past research has shown that the warrior mindset, in particular, can have negative health implications in the long run. The mindset can be costly, not only for the individual and their loved ones, but also for the healthcare services and other agencies. This article draws from a recent interview study with 24 deployed Swedish veterans suffering from deteriorating mental health without receiving a clinical diagnosis. Purposeful sampling was conducted with the support of the medical staff at the Veterans’ Clinic at Uppsala University Hospital. Participants had been screened for posttraumatic stress disorder (PTSD) but had not received a clinical diagnosis. This constitutes a large and understudied patient group in the clinic. The medical staff selected patients based on the following criteria: deteriorating mental health, increased suffering related to PTSD symptoms, and issues related to moral issues, existential concerns, and identity. The sample included veterans from both the Swedish Armed Forces and other deploying agencies. Of the 24 interviewees, 19 were from the Swedish Armed Forces (16 men and three women), and five (four women and one man) were deployed by other agencies. The number of overseas deployments varied widely, with some interviewees having completed 1–2 deployments, while others had completed 3–8. Additionally, some interviewees had interrupted planned or ongoing deployments for various reasons. At the time of the interviews, none were serving full-time in the armed forces; all were veterans. The interviews took place during an intense wave of COVID-19 infections in Sweden in early 2022, so the majority were conducted via videoconference. The participants’ veteran identities were abductively analyzed through the mask of secrecy, the stoic mask, and the mask of denial, which are elements of the “Mask of the Warrior.” This mask functions to safeguard mission focus, to endure, to execute tasks in extremely stressful situations, and to solve operational tasks during deployments and combat operations. The analysis of the interviews suggests that certain elements in these powerful veteran identities can serve as breeding grounds for suffering later in life. The veterans in the study tended to be stoic about their deteriorating mental health, kept the suffering to themselves, and denied the harmful aspects of their deployments. Thus, the Mask of the Warrior played a counterproductive role for the individual, their friends and family, and life in the aftermath of deployments. Another implication of secrecy and denial occurred on the societal or macro and system levels due to the absence of sufficient insight, knowledge, and understanding of veterans among personnel within the healthcare system and other agencies. This made it difficult for the healthcare system, and other relevant agencies, to offer adequate care and to understand the participants’ health issues during sick leave. The perceived absence of societal and organizational rewards and benefits for veterans who risk their mental health and lives during deployment can be seen as a failing implicit work contract. This lack of recognition may lead to the corrosion of character.